2013
DOI: 10.1128/mbio.00569-12
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic De Novo Assembly of an Aquatic Representative of the Verrucomicrobial Class Spartobacteria

Abstract: The verrucomicrobial subdivision 2 class Spartobacteria is one of the most abundant bacterial lineages in soil and has recently also been found to be ubiquitous in aquatic environments. A 16S rRNA gene study from samples spanning the entire salinity range of the Baltic Sea indicated that, in the pelagic brackish water, a phylotype of the Spartobacteria is one of the dominating bacteria during summer. Phylogenetic analyses of related 16S rRNA genes indicate that a purely aquatic lineage within the Spartobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 74 publications
(81 reference statements)
4
87
1
Order By: Relevance
“…supports biogeographic and genomic evidence suggesting that certain marine Verrucomicrobia species have a preference for phytoplankton-derived HMW-DOM (Herleman et al, 2013). Verrucomicrobia have also been identified as degraders of polysaccharides in the Arctic (Cardman et al, 2014) and given their ubiquity in the ocean and presence on POM (Freitas et al, 2014), chemoheterotrophic activity of Verrucomicrobia taxa should contribute markedly to DOM and POM turnover.…”
Section: Discussionmentioning
confidence: 57%
“…supports biogeographic and genomic evidence suggesting that certain marine Verrucomicrobia species have a preference for phytoplankton-derived HMW-DOM (Herleman et al, 2013). Verrucomicrobia have also been identified as degraders of polysaccharides in the Arctic (Cardman et al, 2014) and given their ubiquity in the ocean and presence on POM (Freitas et al, 2014), chemoheterotrophic activity of Verrucomicrobia taxa should contribute markedly to DOM and POM turnover.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, a genome rich in glycoside hydrolases was also reported for the taxon "Candidatus Spartobacteria baltica" within the Spartobacteria (44), suggesting that polysaccharide hydrolysis is widely distributed across the Verrucomicrobia. The polysaccharides laminarin and xylan, which attached to Verrucomicrobiaceae cells in single-cell sorting experiments (77) and constituted some of the inferred substrates for the hydrolases of "Candidatus Spartobacteria baltica" (44), accounted for 15 to 28% of the integrated hydrolysis rates for all substrates measured in Smeerenburgfjord seawater and 41 to 48% of the integrated rates for sediment samples, respectively (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The Verrucomicrobia (38) include the family Verrucomicrobiaceae-congruent with intraphylum subdivision 1 (39)-which harbors the carbohydrate-degrading genus Verrucomicrobium sensu stricto, defined by its possession of cytoplasm-containing cell wall extensions, or prosthecae (40), the prosthecate carbohydrate degraders within the genus Prosthecobacter, isolated from freshwater habitats (41), and several marine heterotrophic genera and species that have been isolated from marine sediment, sponges, algae, and seawater (42,43). The class Spartobacteria (subdivision 2) contains the brackish water taxon "Candidatus Spartobacteria baltica," represented by a genome assembled from an environmental metagenome in Baltic seawater (44), and the heterotrophic soil isolate Chthoniobacter flavus and multiple related isolates from the same pasture soil (45); soil isolates from the same source also constitute the so-far unnamed subdivision 3 (46). Subdivision 4 includes the obligate anaerobe Opitutus terrae and multiple phylotypes from paddy soil (47) and the aerobic seawater and coral-associated species Coraliomargarita akajimensis, as well as the facultative anaerobe Alterococcus agarolyticus (48) and the highly unusual epixenosomes; these bacterial epibionts of the marine ciliate Euplotidium undergo a complex life cycle, possess microtubulins, and form an extrusive apparatus that ejects portions of the bacterial cytoplasm and genome tethered to a 40-m-long tube (49).…”
mentioning
confidence: 99%
“…U copiosus genome is ∼94% complete, based on domain-specific single-copy housekeeping genes commonly used to estimate genome completion 23 (Supplementary Table 3). This list of single-copy genes has been used to estimate genome completeness in several recent studies 13,63 . When we analysed the genome using another metric of genome completeness (checkM 64 ), the results suggested that the genome was 80% complete with 4% contamination, a level categorized as a 'substantially complete draft with low contamination'.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the class Spartobacteria contains only a single described and sequenced isolate, Chthoniobacter flavus, a slow-growing aerobic heterotroph capable of using common components of plant biomass for growth 11,12 . Although Spartobacteria are prevalent in soils, they have also been observed in marine systems ('Spartobacteria baltica') 13 and as nematode symbionts (genus Xiphinematobacter) 14 .…”
mentioning
confidence: 99%